Strategizing for survival – enablers of South African not-for-profit organization sustainability - Ingrid Vorwerk Marren; Annemarie Davis; Charmaine M. Williamson (Cogent Business & Management, 2024)
This article reports on research within multiple case studies of South African Not-for-Profit Organizations (NPO). The study modelled the enabling practices that managers and leaders of these NPOs deem necessary to sustain their service-led organizations in a changing and demanding environment. NPOs face various constraints affecting their survival, including those linked to people and talent, finances, resources, volunteering, and the ever-growing demand for social care. These constraints require managers and leaders of NPOs to identify enabling practices for survival, success, and sustainability. Daily routines in pursuit of strategies demonstrate apex fit-for-practice activities (a concept coined for this study) that include leadership, governance, organizational culture, resources and adaptivity. These activities translate into fit-for-purpose services for the ever-changing needs of beneficiaries. While corporates often focus on excellence and competitive advantage, the NPOs distinguished themselves through adaptable practices that instead met fitness criteria. This approach ensured the survival of NPOs in shrinking resource environments, and the continued service to beneficiaries. These enabling practices contribute to a conceptual model depicting the enablers for long-term survival in the NPO sector, as a novel contribution to the NPO sector, while also theorizing the nexus between fit-for-practice and organizational life cycle.
Keywords: 650; Not-for-profit organizations; fit-forpractice; resilience; survival; organizational lifecycle; multiple case study; sustainability